Pengaruh Manajemen Sumber Daya Manusia dan Kepuasan Kerja Terhadap Kinerja Karyawan UMKM di Kota Padang - Dedi Wandi; Faradilla Suretno; Nesi Afriani Helsya; Sri Wahyuni Lubis; Yefrinal Andra (Jurnal Ilmu Sosial, Ekonomi dan Pendidikan, 2026)
This study aims to examine the influence of Human Resource Management and Job Satisfaction on Employee Performance in MSMEs. The study employed a quantitative approach. The sample consisted of 120 MSME employees, selected using a simple random sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using SPSS version 22. The results indicate that Human Resource Management and Job Satisfaction have a positive and significant influence on Employee Performance, both partially and simultaneously.